Web-Based Administrative Completeness Information System At Badan Pusat Statistik Of Tanah Laut Regency - Prastyaningsih, Yunita; Nurmalia, Isma; Sayyidati, Rabini (Yayasan Insan Mulia Bima, 2025)
Badan Pusat Statistik (BPS) of Tanah Laut Regency needs an administration completeness system, especially for its employees, to facilitate them in viewing the requirements for organizing or participating in activities without any shortcomings. Previously, employees found it difficult to know what requirements had to be fulfilled to organize or participate in an activity. Currently, the administration completeness process is still carried out using Excel files, which are shared via WhatsApp to each employee. Based on this case, a web-based administration completeness information system for employees is developed. The purpose of this case is to analyze, build, and test the web-based administration completeness information system for employees with access rights for two users, namely admin and employees. The methods used are literature study, interviews, and observations. For data collection and system development methods, the waterfall method is used. This system uses an Entity Relationship Diagram (ERD) with 13 tables and system modeling using Unified Modeling Language (UML), including Use Case, Class diagram, Sequence diagram, and Activity diagram. The system is built using CodeIgniter 3 framework with PHP programming language and MySQL database management system. Subsequently, system testing is conducted using Black Box Testing with the result that the web-based administration completeness information system runs according to its functionalities. The result of the system built is that it can help make it easier to manage administrative completeness and help the admin in ensuring that all requirements are met.